The tri-learning modes model: A proposal in the design of materials for a theology course - Lalisan, Salvador June P. (Animo Repository, 2004)
This study aimed at finding out how the Tri-learning model or the TLM-model proposed by the researcher may be applied to the design of materials for a theology subject. It further aimed to find out how the participant-respondents respond to this kind of materials and to see how the use of these materials make the participant-respondents integrate faith to their real-life experiences. The study was conceived in order to provide solutions to the problems besetting the teaching of Theology in the Philippines today as identified in a nationwide survey conducted in 2000-2001 by the Catholic Educators Association of the Philippines and the Social Research Center of the University of Santo Tomas. This interpretive and descriptive qualitative study was conducted with St. Scholastica's College as the locale while adopting a single case-group study method. The participants were thirty students from one class of freshwomyn in Theology 1, Revelation adn Faith Journey. The manner of selection was purposive since all of the participants except for two have had ten years of exposure to religious education. To answer the research questions, several research instruments such as inventories, surveys, questionnaires, templates, observation guide, interview schedule, journals, and projects were used in the study. Documentation and holistic description of the participants' response to the TLM-based materials were done using observation, interview, and document analysis. Data gathered in the study were analyzed by establishing recurring patterns of responses, commonalities in observed behavior, and quality output. In order to ensure validity and reliability of data, a number of strategies were also used: triangulation, member checks, and peer review. Qualitative and quantitative data gathered from the different research instruments revealed several findings. The use of the TLM-model allowed the researcher-designer to create activities that target specific needs of students thus making the materials student-centered. The model also necessitated a match between the learning styles of students and the teacher's teaching styles resulting to experience of success for both the learners and the teachers. Furthermore, it was found out that the TLM-based materials yielded a generally positive response from the participant-respondents. The materials made the study of the Theology subject more exciting, enjoyable, interesting, challenging, useful, relevant, and meaningful. Responses of the participants showed that the materials developed based on the model were able to address the three domains in the learning taxonomy-the cognitive, the affective, and the psychomotor domains. This shows that the TLM-based materials provided for the holistic development of the learners. The TLM-based materials allowed for the creation of activities concentrations to students' own experiences. The materials enabled the learners to apply their learnings of theological concepts to arrive at realizations about themselves, their relationships with friends, with their families and with God. Their insights about their faith were made possible by the concepts that they have learned. The TLM model produced activities that can integrate faith to the students' life experiences. The above findings permitted several conclusions: 1. The TLM-based model may provide the solution to the problem identified to be besetting Religious education today. The model may be used as basis for creating materials that may make the subject more appealing or interesting to most students. It may serve as answer to the top three problems identified in the nationwide survey on the state of religious education in Catholic schools that was conducted in school year 2000-2001 as a joint project of the Catholic Educators Association of the Philippines and the Social Research Center of the University of Santo Tomas. The TLM-based materials may address the lack of interest from students , lack of instructional materials , and the lack of adequate training and preparation among religious educators since findings of the study showed that the materials made the learning of the theology subject interesting , exciting , enjoyable , fun , challenging , and relevant . 2. The use of TLM-based materials will make religious education responsive to its societal role of forming the total human person in order to bring about relevant changes in the society since the materials allowed the integration of concepts learned and lived experiences. 3. Learning becomes more meaningful and relevant when it is approached from the affective route as revealed by the positive responses of the participant-respondents. 4. Addressing the needs of learners may become more manageable if there is a model, in this case, the TLM model, to use as guide. It has always been said that the best way to respond to the needs of the learners is to know what they need. However, this prescription is difficult to follow in the absence of a model that is friendly to teacher-users. The TLM-model since it presents in detail the steps to follow may be the model that fills that need. 5. The TLM-based materials are different from the typical materials that are currently in use. The materials addressed in equal importance the three most important elements in the teaching-learning process, namely the activities, the strategies, and the recipient of instruction. 6. The TLM-based materials that take into account the learners intelligences and learning styles and that of the teachers teaching styles-positively rewarded both the teachers and the learners in that the learners enjoy learning while the teachers find fulfillment in what they do. Based on the above findings and conclusions the following recommendations were made: 1. Encourage future researches to make conclusive what was explored, observed, described, and interpreted in this study. 2. Further research on the applicability of the TLM-based materials need to be done in order to establish its suitability to all types of learners and all theology subjects. 3. Experimental research to establish the effectivity of the TLM-based materials in producing significant gains in learning theological concepts must be conducted to directly attribute significant results to the materials. 4. Correlation studies between exposure to TLM-based materials and the development of Multiple Intelligences and Learning Styles among students must be conducted in order to find out if the materials indeed are instrumental in the development of underdeveloped intelligences and less favored learning styles. 5. A TLM-based curriculum for different levels in Religious Education and Theology must be taken into consideration. 6. The applicability of the TLM-based materials to other disciplines must also be studied. 7. There is a need to develop templates using the TLM-model for all theology subjects in various levels. 8. Training programs on the use of the TLM-based materials is highly recommended among teachers and catechists. 9. Exploration of the integration of the TLM model in other disciplines and in training programs for employers in the corporate venue must also be considered. 10. There is a need to explore the integration of the TLM model in liturgical and paraliturgical celebrations. 11. Experiment on the use of the TLM model in different levels of the academe must be considered.